Determinan Prioritas Pembelian Perumahan Subsidi di Kota Langsa Menggunakan Metode Analytical Hierarchy Process - Qusyairi Ahmadi; Meilandy Purwandito; Firdasari Firdasari; Nova Purnama Lisa (Fakultas Teknik, 2023)
The construction of subsidized housing in Langsa City has increased, yet it fails to bridge the gap between housing demand and supply, especially in metropolitan areas. To ensure the development of subsidized housing benefits the community, careful attention is required. This study aimed to identify the most suitable area for subsidized housing and its requirements in Langsa City. Using the Analytical Hierarchy Process (AHP), the study assessed five criteria: accessibility, facilities and infrastructure, environmental conditions, buildings, and subsidized house prices. The AHP findings achieved a consistent index of 7%, meeting the required threshold. Results revealed that accessibility holds the highest weight (0.33), followed by facilities and infrastructure (0.20), environmental conditions (0.19), building conditions (0.17), and house prices (0.11). This highlights accessibility as a significant factor in purchasing subsidized housing in Langsa City. Langsa Barat District emerged as the best-fitted location for subsidized housing, with a weight value of 4.09. Despite increased construction efforts, addressing the housing demand and supply gap remains a challenging task in Langsa City's metropolitan areas.